PENGARUH UKURAN LEGISLATIF, TINGKAT KETERGANTUNGAN PEMERINTAH DAERAH, DAN TINGKAT KEKAYAAN PEMERINTAH DAERAH TERHADAP RASIO EFEKTIVITAS KINERJA KEUANGAN PEMERINTAH KABUPATEN/KOTA PROVINSI SUMBAGSEL - Anisa Musdirohmah; Sunardi Sunardi; Yulian Sahri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the size of the legislature, the level of dependence of the local government, and the level of wealth of the local government on the Effectiveness Ratio of the Financial Performance of the Regency / City Government of SUMBAGSEL Province. The type of research used in this research is associative research. The population in this study was 60 regencies/cities in the provinces of South Sumatra, Lampung, Bengkulu, Jambi, and Bangka Belitung Islands, with the sample method determined was the saturated sample. The data used is secondary data in the form of LKPD in 2018-2020. The data collection method in this research is the documentation method. The data analysis method used is descriptive statistical analysis method, classical assumption test and multiple linear regression, as well as data processing in this research using SPSS 26.0 (Statistical Product and Service Solution) statistical computer program. The results of this study can be concluded that partially (t test) shows that the size of the legislature and the level of dependence of the local government have no effect on the ratio of the effectiveness of the financial performance of the district/city government of SUMBAGSEL Province, while the level of local government wealth has a significant effect on the ratio of the effectiveness of the financial performance of the district/city government. city of SUMBAGSEL Province.